Penggunaan Media Video dalam Pendidikan Kesehatan tentang Cuci Tangan Pakai Sabun pada Era Normal Baru COVID-19 bagi Siswa Sekolah Dasar - Janah, Esti Nur; Hamdi, Mashudi (Health Information : Jurnal Penelitian, 2022)
Background: Children can become carriers in the chain of transmission of the Covid-19 virus, so that they can endanger vulnerable populations. Prevention efforts that can be done is to get used to washing hands properly, especially washing hands with soap. In Brebes Regency, only 50% of elementary schools have handwashing facilities. Of this number, only 10% of schools have provided hand washing soap facilities, even though Brebes Regency is one of the districts that has received the Community-Based Total Sanitation (STBM) program since 2013 which is still running today. The purpose of this study was to determine the effect of health education using video media on knowledge of hand washing using soap in the new normal era of Covid-19 in elementary school students 2022. Method: The design in this study is a pre-test design and post-test design. The population of this study were students of grades IV, V and VI MI Darul Ulum Kalilangkap with a total of 52 people. Sampling using total sampling where the number of samples is equal to the total population, namely 52 people. Result:Based on the results of the Paired T Test statistical test, it was found that p-value = 0.000 (<0.05). Conclusion: there is an effect of health education using video media on knowledge of Handwashing with Soap in the New Normal Era of Covid-19 in students. The research results can be followed up with efforts to increase the provision of more adequate hand washing facilities.